Cell Cycle Dysregulation and Renal Fibrosis - Wu, Yun-Shan; Liang, Shan; Li, Dong-Yi; Wen, Jun-Hao; Tang, Ji-Xin; Liu, Hua-Feng (Frontiers in Cell and Developmental Biology, 2021)
Precisely regulation of cell cycle is essential for tissue homeostasis and development, whereas cell cycle dysregulation is involved in many diseases including renal fibrosis, which is a common pathway of various chronic kidney diseases leading to end-stage renal failure. Until now, there are no effective drugs available to treat renal fibrosis. In adult mammalian healthy kidney, most of the renal cells are post-mitotic quiescent cells arrested in the G0 phase of cell cycle. In addition, renal cells turn over is very low. After injury, renal cells are stimulated and enter into cell cycle which is essential for kidney regeneration and renal function restoration. However, if the injury is severe or repeated injuries, cell cycle of renal cells will be dysregulated, manifested as cell cycle arrest or over proliferation, both of which are closely related to renal fibrosis. Thus, cell cycle dysregulation of renal cells represents a potential therapeutic target to treatment of renal fibrosis. In this review, we focus on cell cycle regulation of renal cells in healthy and disease kidney, discuss the relationship of cell cycle dysregulation with renal fibrosis. The better understanding of the mechanism by which cell cycle dysregulation of renal cells drives renal fibrosis is essential for the development of therapeutics to halt renal fibrosis progression or promote regression.